Experiential Marketing: A Conceptual Framework for Connecting with the Customers - Nair, Lakshmi (Indian Journal of Marketing, 2010)
It takes a marketer to recognize the blessing and the curse that lies behind the saying: ’May you live in interesting times.’ Today’s interesting times are marked by dramatic societal changes, and the breathtaking technological breakthroughs that are instrumental in pushing them, and have opened a vast spectrum of opportunities, challenges and demands for the marketing profession. In this rapidly evolving environment, the number of levers that must be pulled to reach the customer are growing rapidly. Technology has not only helped to fuel this expansion, but has opened up the vistas in expanding marketing’s ability to tap into the possibilities more creatively and effectively than ever before. It enables a richer understanding of customers’ expectations of, and interactions with, a brand, giving the business deeper insights into ways to better harness the relationship to create business growth. It creates the means for more personalized, one-on-one interactions and experiences with the brand. But the pressure is also on marketing to think more strategically in light of all these changes: about how to marry the ’art and science’ that come with the job more effectively; about ways to demonstrate its relevance and expand its role outside its traditional sphere of influence; about how marketing can quantifiably contribute to the business’s long-term success.